FENOMENA CATCALLING DI LINGKUNGAN FKIP P.IPS UNIVERSITAS RIAU SEBAGAI BENTUK PELECEHAN VERBAL DAN DAMPAKNYA TERHADAP KENYAMANAN MAHASISWA - Nur Husna, Latifa; Ramadhani, Aulia; Selima Salsabila, Fyka; Ferdinand, Ridho; Tulhusna, Izzah; Hartasya, Syely; Raisa, Raihana; Agustian Saputra, Dino; Dinda Sarmita Harahap, Rizky; Hambali (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Catcalling, a form of verbal harassment commonly experienced in public spaces, including on campus, was the focus of this research within the Social Sciences Education Study Program (PIPS) at the University of Riau. A combined qualitative descriptive approach and student survey findings were employed, with data collected through intensive interviews, participant observation, document review, and questionnaires from active PIPS students. Key findings revealed diverse forms of catcalling, ranging from whistling and comments about physical appearance, sexually suggestive names, to demeaning non-verbal cues. The survey showed that most female respondents had experienced or witnessed these incidents, particularly around the campus lake, corridors, and parking lots in the late afternoon. The consequences include emotional unrest, limited mobility, decreased self-confidence, and disruption to academic engagement. The uncovered triggers reflect the normalization of patriarchal culture, a lack of gender awareness, an indecisive institutional response, and the absence of effective complaint channels. Therefore, this research advocates comprehensive interventions through strengthening regulations, gender education for change, and empowerment of the campus community.